Experimental investigation of the influence of internal frames on the vibroacoustic behavior of a stiffened cylindrical shell using wavenumber analysis. (1st September 2017) - Meyer, V.; Maxit, L.; Renou, Y.; Audoly, C.
Highlights: Scanning laser vibrometer measurements on a stiffened cylindrical shell. Analysis in the wavenumber domain using 2D Fourier transforms. Study of the effect of a non-axisymmetric internal frame. Explanation of the physical mechanisms of the increase in radiation efficiency. Abstract: The understanding of the influence of non-axisymmetric internal frames on the vibroacoustic behavior of a stiffened cylindrical shell is of high interest for the naval or aeronautic industries. Several numerical studies have shown that the non-axisymmetric internal frame can increase the radiation efficiency significantly in the case of a mechanical point force. However, less attention has been paid to the experimental verification of this statement. That is why this paper proposes to compare the radiation efficiency estimated experimentally for a stiffened cylindrical shell with and without internal frames. The experimental process is based on scanning laser vibrometer measurements of the vibrations on the surface of the shell. A transform of the vibratory field in the wavenumber domain is then performed. It allows estimating the far-field radiated pressure with the stationary phase theorem. An increase of the radiation efficiency is observed in the low frequencies. Analysis of the velocity field in the physical and wavenumber spaces allows highlighting the coupling of the circumferential orders at the origin of the increase in the radiation efficiency.